RIBA (USURY OR TAKING AND CHARGING INTEREST) - Solikhul Hadi (Program Studi Hukum Keluarga Islam, 2014)
Riba is an exchange of Ribawi elements where there is a difference in time and/or quantity. The Ribawi elements mentioned by the prophet are gold for gold, silver for silver, wheat for wheat, barley for barley, dates for dates, and salt for salt. By a similar analogy, money is similar to gold and silver which is a modern way of exchange. Therefore a contract of exchange between the insurer and insured contains a Ribawi element, i.e. levels of compensation involving varying amounts and time scales. The strict prohibition of interest in Islam is because of the following reasons (Qaradawi, 2001 ). Taking of interest implies appropriating another person’s property without giving them anything in exchange, because the one who lends the other one dollar receives one extra dollar for nothing. Dependent on interest prevents people from working to earn money since the person with one dollar can earn extra dollars through interest either in advance or on later date without working for it. If it is happen to capital owner then they would not invest in the industry, trade and commerce, building and construction, as they will get extra earning without necessarily doing all of the hard work. Permitting the taking of interest discourages people from doing good deeds to others. If interest is prohibited in a society, people will lend to each other with a good will, expecting back no more then what they have lent. Riba is also totally prohibited in Islam because it tends to create unfair or injustice treatment between one party with another. It also exploits one by the others. In Ribawi economic the rich one tends to get more benefit compares with the poor one. The gap between the rich one and the poor one is becoming bigger and bigger as Riba have a spiral impact on increasing price for goods.